An endogenous potential of Poland and its regions - Koza, Iwona (Management and Administration Journal, 2019)
In this article I will present a brief introduction to the issues of innovation, intellectual capital, knowledge-based economy and entrepreneurship and human resources management. Research results were presented relating to Poland in comparison to the European Community. The results of the study of regional innovation for Polish regions will be presented to select some of them. It was decided on two regions with very different economic performance, i.e. Malopolskie and Mazowieckie provinces. In the course of the work, the entities examined have been found to be modest or moderate innovators. Delays has been observed in the sphere of infrastructure, availability of transport or advanced services. A unique opportunity for provinces and the whole country seems to be the intellectual capital, mobility, agility and dynamism of rapidly gaining new skills by the young generation. A good method to think in a creative way about the future of the regions, and at the same time create a conceptual framework for strategic policy in the region seems to be foresight studies.